2003
DOI: 10.1016/j.stam.2003.12.007
|View full text |Cite
|
Sign up to set email alerts
|

Removal of phosphorus by the solidification refining with Si—Al melts

Abstract: To discuss the possibility of phosphorus removal from silicon by the solidification refining with Si -Al melts, the distribution of phosphorus between solid silicon and the liquid Si-Al alloy at 1173-1373 K was investigated. In the present study, the distribution of phosphorus was examined by the temperature gradient zone melting method, where a phosphorus containing molten Si -Al zone was passed through a single crystalline silicon phase. The segregation ratio of phosphorus at its infinite dilution was obtain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
34
0
1

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 129 publications
(36 citation statements)
references
References 16 publications
1
34
0
1
Order By: Relevance
“…В работах [4][5][6] показано, что зависимость коэффициентов сегрега-ции k(T ) компонентов B, P от температуры в системе Si-Al с высокой точностью можно считать линейной:…”
Section: фазовая диаграммаunclassified
“…В работах [4][5][6] показано, что зависимость коэффициентов сегрега-ции k(T ) компонентов B, P от температуры в системе Si-Al с высокой точностью можно считать линейной:…”
Section: фазовая диаграммаunclassified
“…Yoshikawa and Morita proposed the methods for the removal of boron 3,4) and phosphorus 5) by addition of Al and Ti. Shimpo et al 6) and Inoue et al 7) reported the Ca addition method to remove boron and phosphorus in silicon.…”
Section: Retrograde Solubilitymentioning
confidence: 99%
“…At present, an expensive grade of silicon for semiconductor is used for solar cell to convert solar energy into electricity. The use of expensive raw material for photovoltaic industry results in a high cost of photovoltaic electricity, the cost of which is five-time higher than that of the electricity from conventional electricity generation [2][3][4].To upgrade metallurgical silicon to solar grade silicon, a great number of research works have been carried out in this field of using relative inexpensive raw material, metallurgical grade silicon, as a starting materials for the production of solar grade silicon is one of the most economical way to make solar cells [1][2][3][4][5][6]. Solidification refining is an effective way to remove most impurities in molten silicon, which doesn't need any chemical reaction, with the exception of phosphorus and boron [7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%